Anatomical Consideration of Dhamani Marma with SpecialReference to Vidhur Marma in Ayurveda - Bhatt, Akanksha (International Research Journal of Ayurveda & Yoga, 2024)
Marma sharira is known as the science of traumatological anatomy. Injuries to various structures of the body such as arteries, muscles, nerves, bones, and visceral organs may result in fatal injuries and death. Marmas in Ayurvedic classics are illustrated as the vital points in human body injury of which leads to termination of life. Acharya Sushruta has presented five types of marmas on structural basis, that is, Mansa-marma, Sira-marma, Snayu-marma, Asthi-marma, and Sandhi marma. Whereas according to acharya Vaghbhatt, there are six types of marmas. He has enumerated a sixth group of marma known as Dhamani Marma. Under the Dhamani Marmas which are nine in number he has presented Vidhur marma. The injury to which leads to deafness. The possible cause of deafness may be due to injury of an arterial structure that is Dhamani or snayu, that is, nerves. This article focuses on co-relating various anatomical structures such as arteries and nerves with Dhamani Marma explained by acharya Vagbhatt with special reference to Vidhur marma injury.